Software development for aerodynamic characteristics estimation of wing-body combination of aircraft at cubsonic speeds - Dahalan, Md. Nizam (Faculty of Mechanical Engineering, 2001)
The study of aerodynamic characteristics is an important aspects in designing of an aircraft. The estimate of the lift and drag coefficients of the combination of wings and bodies at subsonic speeds. The calculation of these aerodynamic characteristics is a tedious workout in the preliminary design, as it has to be carried out repetitively for every different combination. A software for determining the wing-body combination lift and drag coefficients known as AC Estimator is being developed to serve as a solution to the tedious and time-consuming design method. The development and capabilities of this software to predict varieties aerodynamic characteristics with good accuracy as compared to manual calculation are being presented and discussed in this paper.